Paradigms in Swedish as a second language – Curricula for primary school and secondary school in swedish as a second language - Ulrika Magnusson (International Electronic Journal of Elementary Education, 2013)
This article analyzes and compares the curricula of Swedish and Swedish as a second language for primary and secondary school. The school subject of Swedish as a second language is young, and its ideological foundation has not been debated to any large extent, in contrast to Swedish. This article analyzes the curricula of both subjects in terms of “paradigms”, i.e. beliefs and conceptions on a school subject, and the Appraisal system developed within the framework of Systemic functional linguistics. In comparison, the curriculum of Swedish as a second language turns out to be more oriented towards skills and communicative paradigms, at the expense of paradigms related to personal growth, literature or Bildung. Also, the curriculum seems to have weak connections to research on second language development or education. The article also gives an overview of the Swedish school system with special focus on education for immigrants and multilingual students.